Isomorfismo nas práticas de gestão ambiental em duas grandes organizações do complexo mínero-siderúrgico do Espírito Santo. - Diniz, Clarkson Machado (2003)
The objective of this dissertation is to comprehend, through the study in two grand mineral-siderurgical organizations, how the structure of their environmental management systems processes, in order to attend the pressure of their organizational field, a